Mapping of Warehouse Radio Frequency Identification Research: A Bibliometric Analysis - Auliana, Windi; Qurtubi, Qurtubi; Setiawan, Danang; Elquthb, Jundi Nourfateha (Bright Publisher, 2024)
Warehouses play a vital role as an intermediary between entities in supply chains, connecting upstream and downstream entities. Implementing Radio Frequency Identification (RFID) technology as a warehouse management system enables data collection with more accuracy, speed, and reliability. This research was motivated by the limited bibliometric perspective and visualization of research on warehouse RFID. The use of bibliometric methods aimed to find basic patterns and an overview of the direction of research related to warehouse RFID. This research utilized the Publish or Perish and VOSviewer tools for analyzing purposes. This study comprised 172 Scopus journals that provide an extensive overview of the developmental progress over 2003-2023 period. Bibliometric visualization was conducted to investigate the outcomes from later publications connected to warehouse RFID. The visualization displayed the leading publishers, yearly patterns, prominent publication titles, top authors, most referenced papers, distribution of keywords, most influential journals, and areas of research that require more investigation.